Perceived car dependence and multimodality in urban areas in Flanders (Belgium) - Van Eenoo, Eva; Fransen, Koos; Boussauw, Kobe (European Journal of Transport and Infrastructure Research, 2022)
In this study, we test the extent to which people who reside in hypothetically car-independent neighbourhoods travel multimodally and perceive themselves as car dependent. We used the Flemish region as our study case, and defined a car-independent neighbourhood as an area with a high node and a high place value. A cluster analysis with four constituent variables – car use frequency, bicycle use frequency, vehicle kilometers travelled (VKT) and the need for a car to carry out daily activities - led to defining four heterogeneous groups of car owners. We labelled the groups as car-dependent motorists - long distance, car-dependent motorists - short distance, car-independent cyclists and car-dependent cyclists. We found all clusters to be to some extent multimodal. For our selected study area, car ownership does not necessarily induce perceived car-dependence among people who can easily get around by bicycle. Nevertheless, even in an urban setting and when exhibiting multimodal travel patterns, people can perceive their car as indispensable. Perceived car dependence is not necessarily correlated with high VKT or high frequency of car use, neither can we conclude that multimodal behaviour necessarily leads to less VKT.